Porous carbon nanofibers containing silica-coated iron oxide nanoparticles by carbonisation of electrospun amphiphilic copolymer nanocomposites - Van Niekerk, Marthinus Gerhardus Mynhardt (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.